UJI TOKSISITAS (LC50 – 24 JAM) EKSTRAK KULIT JENGKOL Pithecellobium jiringa) TERHADAP LARVA UDANG Artemia salina Leach - Indah Sinaga; Rosliana Rosliana; Riyanto Riyanto (JBIO: jurnal biosains (the journal of biosciences), 2018)
The objective of this experiment is to determine the amount of toxicity leves (LC50–24 jam) peel extrack Jengkol (Pithecellobium jiringa) against larvae of the Artemia salina. The observation method consists of three stages : Observasi, Eksploratory, Full scale test. The concentrations used in the observation were 0%, 5%, 10%, and 15%. In the Eksploratory stateg, the concentrations used were 0%, 1%, 3%, 5%, 7%, and 9%. And for the Full scale test concentrations used were 0%, 4%, 4,5%, 5%, 5,5%, and 6%. The result of toxicity test (LC50–24 jam) peel extrack of Jengkol (Pithecellobium jiringa) showed that the optimum dose is 5,5% whic has mortality 51.1% to the larvae of the Artemia salina.